2020
DOI: 10.11594/bbrj.03.02.01
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Education Level, Knowledge and Motivation in Volunteer Performance: a Post-Study on Action Research in Developing Educator Volunteers for COVID-19 Based on community empowerment using a tiered and online platform in Indonesia

Abstract: COVID-19 infection is spreading globally, including in Indonesia. The corona-virus transmits so quickly; there is panic in the community to avoid transmission. Stakeholders could develop educator volunteers based on community empowerment to increase public knowledge so that they can prevent transmission of the Corona Virus. Aims. This study aimed to determine the correlation between education level, knowledge and motivation in volunteer performance after training on developing educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Khuzaiyah and colleagues investigated the correlation between educational level, knowledge, motivation, and volunteer performance in developing educator volunteers for COVID-19 in Indonesia. They found that motivation was significantly correlated with volunteer performance, whereas educational level and knowledge were not 22 . The authors suggested that providing full support for volunteers is crucial in motivating them to carry out their roles as educator volunteers in COVID-19.…”
Section: Community Development Volunteering and Response To The Pandemicmentioning
confidence: 99%
“…Khuzaiyah and colleagues investigated the correlation between educational level, knowledge, motivation, and volunteer performance in developing educator volunteers for COVID-19 in Indonesia. They found that motivation was significantly correlated with volunteer performance, whereas educational level and knowledge were not 22 . The authors suggested that providing full support for volunteers is crucial in motivating them to carry out their roles as educator volunteers in COVID-19.…”
Section: Community Development Volunteering and Response To The Pandemicmentioning
confidence: 99%